Immunohistochemical labeling of the inhibin/activin βC subunit in normal human placental tissue and chorionic carcinoma cell lines - Weissenbacher, Tobias Marcus; Brüning, Ansgar; Kimmich, Tanja; Makovitzky, József; Gingelmaier, Andrea; Mylonas, Ioannis (Journal of histochemistry & cytochemistry, 2010)
Inhibins and activins are important regulators of the female reproductive system. A novel inhibin subunit, named βC, has been identified and demonstrated to be expressed in several human tissues. We demonstrate here that inhibin βC is expressed in human placenta. Expression of the inhibin βC subunit was demonstrated at the protein level by means of immunohistochemical evaluation and at the transcriptional level by an inhibin βC-specific RT-PCR analysis. Expression of inhibin βC was detected in the human chorionic carcinoma cell lines JEG and BeWo. Although the precise role of this novel inhibin subunit in human placenta development and homeostasis is unclear, analogies with other inhibin sub-units and the strong expression of ?C in normal human trophoblast cells and chorionic carcinoma cells suggest that βC may be involved in autocrine/paracrine signaling pathways, angiogenesis, decidualization, and tissue remodeling under normal and malignant conditions. Additionally, JEG and BeWo express βC and, therefore, can be used as a cell culture model for further functional analysis of this subunit in the human placenta.